The induced membrane technique: Optimization of bone grafting in a rat model of segmental bone defect. Issue 6 (June 2022) - Sun, Hening; Godbout, Charles; Ryan, Gareth; Hoit, Graeme; Higgins, James; Schemitsch, Emil H.; Nauth, Aaron
Highlights: We have developed an effective rat model of the induced membrane technique consistent with clinical healing outcomes. Minimizing cancellous bone, inclusion of bone marrow and decreasing donor sacrifice to grafting time resulted in superior healing rates. Our findings will benefit future studies investigating various aspects of the induced membrane technique in small animal models. Abstract: Introduction: The induced membrane technique (IMT) is a two-stage surgical procedure used to treat fracture nonunion and bone defects. Although there is an increasing number of animal studies investigating the IMT, few have examined the outcomes of bone healing after a second stage grafting procedure. This study aimed at comparing two bone grafting procedures, as part of the IMT, in order to establish a rat model providing consistent healing outcomes. Methods: In male Fischer 344 rats, we created a 5 mm defect in the right femur, stabilized the bone with a plate and screws, and inserted a polymethylmethacrylate spacer into the defect. Four weeks later, the spacer was removed. Bone graft was harvested from a donor rat and placed into the defect, followed by membrane and wound closure. Experiments were conducted in two groups. In group 1 ( n  = 11), the bone graft contained a variable amount of cortical and cancellous bone, the time from donor euthanasia to grafting was up to 240 min, and one donor rat provided graft for 5-6 recipients. In group 2 ( n  = 12), we reduced the contribution of cortical bone to the graft, included bone marrow, and kept donor euthanasia to grafting time under 150 min. One donor was used per 3-4 recipients. The volume of graft per recipient and all other elements of the protocol were the same across groups. Bone healing at 12 weeks post grafting was compared radiographically by two orthopaedic surgeons in a blinded fashion, based on union status and a modified Lane & Sandhu score. Results: Healing rates improved from 36.4% in Group 1 to 91.6% in Group 2. There was a significant relationship between the methods and resulting union status ( p  = 0.004). The odds of achieving full union were significantly higher in group 2 compared to group 1 (odds ratio=19.25, 95% confidence interval [1.77-209.55]; p  = 0.009). The average radiographic score was also significantly higher in group 2 ( p  = 0.005). Conclusion: The revised bone grafting method significantly improved the healing outcomes and contributed to establishing a consistent rat model of the IMT. This model can benefit preclinical investigations by allowing for reliable and clinically-relevant comparisons.